Pengaruh Kehadiran Apoteker Terhadap Pelayanan Kefarmasian di Apotek di Kota Padang - Dwi Dominica; Deddi Prima Putra; Yulihasri Yulihasri (Fakultas Farmasi Universitas Andalas, 2016)
Standard pharmacy services is measure used especially in implementing pharmacist pharmacy services. This study examines effect of presence of Pharmacists to pharmacy services, is crosssectional study using questionnaires in February - August2015. The research sample 90 Pharmacists in pharmacies taken random. results Showed the percentage of the presence of the pharmacist in the pharmacy Padang city 58.67% and Pharmaceutical Services Categorized less (inspection recipe 57.06%, 55.12% prescription preparation, and delivery prescriptions 51.89%) with average percentage 54,69%. Linear regression analysis of test results can be known effect X on Y positive. Testing shows the product moment correlation coefficient X to Y Strong where: r=0.910, in testing the coefficient of determination shows X higher influence on Y equal to 82.8% and 17.2% influenced other factors. Based on the F test 422,579 with significance of 0.000. Due significant levels <0.05, can concluded that the presence of Pharmacists have influence on Pharmaceutical Services.